The Hunt for The Secret Papyrus - Stilton, Geronimo (Scholastic Inc., 2017)
Geronimo, Thea, and their cousin Trap explore an old castle built by Grant Gentlemouse, the founder of New Mouse City, and when they find one hundred keys and only ninety-nine doors inside, they set off in search of the missing room.